2008
DOI: 10.2166/wst.2008.081
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of food waste digestion in the hybrid anaerobic solid-liquid system

Abstract: The hybrid anaerobic solid-liquid (HASL) system is a modified two-phase anaerobic digester for food waste treatment. To enhance the performance of anaerobic digestion in the HASL system, thermal pre-treatment (heating at 150 degrees C for 1 h) and freezing/thawing (freezing for 24 h at-20 degrees C and then thawing for 12 h at 25 degrees C) were proposed for food waste pre-treatment before the anaerobic digestion. Both processes were able to alter the characteristics and structure of food waste favoring substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Anaerobic digestion (AD), a biological conversion of organic matter into methane, carbon dioxide, inorganic nutrients and humus-like matter, appears to be the most promising method for FW treatment (Liu et al, 2008). As compared to the aerobic method, the use of anaerobic processes for the waste streams provides greater economic and environmental benefits and advantages (Mohan and Bindhu, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic digestion (AD), a biological conversion of organic matter into methane, carbon dioxide, inorganic nutrients and humus-like matter, appears to be the most promising method for FW treatment (Liu et al, 2008). As compared to the aerobic method, the use of anaerobic processes for the waste streams provides greater economic and environmental benefits and advantages (Mohan and Bindhu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to improve the performance of the reactor by allowing enough buffering capacity and space for respective microbial communities to flourish under suitable conditions. Adding on to this, a two-phase hybrid anaerobic solid-liquid system (HASL) by Wang et al (2002Wang et al ( , 2003 and Liu et al (2008), was studied in detail for FW digestion and has shown promising results. Apart from these reactor types, an up-flow anaerobic sludge blanket process elaborately reviewed by Chong et al (2012) is extensively applied for wastewater treatment with relatively high removal efficiency at short hydraulic retention times (HRTs), but is also considered not suitable for wastes with high solid content such as municipal FW (Tawfik et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of clean water to reduce solid content of FW should be avoided as clean water is valuable commodity in Singapore. Therefore, 20 % of the AD effluent (pH & 7) was recycled to dilute the solid content of FW and increased the pH of feedstock, while 80 % of the AD effluent was used for dilution of the effluent from acidogenic reactor to maintain an optimal pH for further methanogenesis [55].…”
Section: Small-scale Anaerobic Digestionmentioning
confidence: 99%
“…Two pretreatment methods for food waste were evaluated prior to use in a modified two-phase anaerobic digester Ding et al, 2008). The first method was thermal treatment and the second method was freeze/thaw treatment; the pretreatment processes decreased digestion time by 48% and 42% for the first and second methods, respectively.…”
Section: Process Technologymentioning
confidence: 99%